Ranma 1/2. Vol. 15 - Takahashi, Rumiko, 1957- (Viz, 2005)
Author and artist Takahashi, the world's most popular and prolific female manga creator, continues her series about a teenager martial artist name Ranma Saotome. Also an anime series, all seven TV seasons (over 150 episodes) are now available on DVD from Viz.